(untitled) (Revista de Diavulgación L’esprit Ingénieux, 2025)
Stabilization ponds, and facultative ponds specifically, provide an optimal solution for wastewater treatment, focusing on the removal of BOD through various natural processes and pre-designed elements. When analyzing the factors that are most relevant in designing a facultative pond, the importance of retention time in relation to the depth at which the pond is designed was found. Taking these values into account, it was determined that the retention time is directly proportional to the depth, resulting in linear growth. This way, the possibility of studying the depth in more detail prior to the construction of a pond is analyzed in order to obtain appropriate retention times and efficiency in the purification of treated water.